PENGARUH REPUTASI MERK, KESADARAN MERK, DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN DI HONDA MOTOR (STUDI PADA KONSUMEN ASTRA MOTOR CENTER SEMARANG) - Alesandro, Alesandro Taruna Wijaya; Amron (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study aims to analyze the influence of Brand Reputation, Brand Awareness, and Advertising on Consumer Purchasing Decisions. The study was conducted using a quantitative approach with structural model analysis (SEM) techniques through the SmartPLS application. The results of the analysis show that the three independent variables have a significant effect on purchasing decisions, with T-statistic values ​​above 1.65 and P-values ​​below 0.05. The R-square value of 0.831 indicates that 83.1% of the variation in purchasing decisions can be explained by the variables in the model. These findings indicate that a marketing strategy that prioritizes good brand reputation, high brand awareness, and targeted advertising propaganda is very important in driving consumer purchasing decisions. This study provides a practical contribution to business actors in designing more effective marketing communication strategies.